Potential distribution and geographic characteristics of wild populations of Vanilla planifolia (Orchidaceae) Oaxaca, Mexico - Hernandez-Ruiz, Jesús (2016)
Wild specimens of Vanilla planifolia represent a vital part of this resource primary gene pool, and some plants have only been reported in Oaxaca, Mexico. For this reason, we studied its geographical distribution within the state, to locate and describe the ecological characteristics of the areas where they have been found, in order to identify potential areas of establishment. The method comprised four stages: 1) the creation of a database with herbarium records, 2) the construction of the potential distribution based on historical herbarium records for the species, using the model of maximum entropy (MaxEnt) and 22 bioclimatic variables as predictors; 3) an in situ systematic search of individuals, based on herbarium records and areas of potential distribution in 24 municipalities, to determine the habitat current situation and distribution; 4) the description of the environmental factors of potential ecological niches generated by MaxEnt. A review of herbarium collections revealed a total of 18 records of V. planifolia between 1939 and 1998. The systematic search located 28 plants distributed in 12 sites in 95 364 Km2. The most important variables that determined the model of vanilla potential distribution were: precipitation in the rainy season (61.9 %), soil moisture regime (23.4 %) and precipitation during the four months of highest rainfall (8.1 %). The species potential habitat was found to be distributed in four zones: wet tropics of the Gulf of Mexico, humid temperate, humid tropical, and humid temperate in the Pacific. Precipitation oscillated within the annual ranges of 2 500 to 4 000 mm, with summer rains, and winter precipitation as 5 to 10 % of the total. The moisture regime and predominating climate were udic type I (330 to 365 days of moisture) and hot humid (Am/A(C) m). The plants were located at altitudes of 200 to 1 190 masl, on rough hillsides that generally make up the foothills of mountain systems, with altitudes of 1 300 to 2 500 masl. In natural conditions, distribution of the species is not limited to high evergreen forests, since it was also found in mountain mesophyll and tropical evergreen forests. The location of new specimens of V. planifolia in its wild condition reduces the potential distribution area by 66 %. This area is fragmented into three geographically separated areas. Habitat reduction was due to the increased number of located plants that define the environmental conditions into a more accurate level. Conservation actions can thus be designed and implemented, focusing on more specific areas within the state of Oaxaca, Mexico.